Modern forms : a subjective atlas of 20th-century architecture - Grospierre, Nicolas, 1975-; Pardo, Alona; Redstone, Elias; Mazur, Adam (Munich : Prestel, 2018)
'Now available in a new compact edition, this book offers a stunning visual archive of nearly 200 images of modern architecture by award-winning photographer Nicolas Grospierre ... Derived from his popular blog, A Subjective Atlas of Modern Architecture, and organized by architectural form, this book reveals how modernist architecture is the embodiment of political and social ideologies, especially in public institutions such as banks, churches, libraries and government buildings.'--From publisher's web site.
Texts : Modern forms / Alona Pardo, Elias Redstone -- The monogrammist'NG' / Adam Mazur -- Pictures -- Index.
Includes index.
Keywords: Modern movement (Architecture) -- Pictorial works; Architectural photography